2018
DOI: 10.1371/journal.ppat.1007315
|View full text |Cite
|
Sign up to set email alerts
|

The trypanocidal benzoxaborole AN7973 inhibits trypanosome mRNA processing

Abstract: Kinetoplastid parasites—trypanosomes and leishmanias—infect millions of humans and cause economically devastating diseases of livestock, and the few existing drugs have serious deficiencies. Benzoxaborole-based compounds are very promising potential novel anti-trypanosomal therapies, with candidates already in human and animal clinical trials. We investigated the mechanism of action of several benzoxaboroles, including AN7973, an early candidate for veterinary trypanosomosis. In all kinetoplastids, transcripti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 88 publications
7
59
0
Order By: Relevance
“…The benzoxaborole acoziborole is undergoing clinical trials for sleeping sickness treatment [113], and other benzoxaboroles are under consideration for other kinetoplastid diseases [114]. The first detectable effect after treatment of T. brucei with the benzoxaborole AN7973 is an increase in mRNA precursors and a decrease in the Y-structure intermediate [3], suggesting that this compound targets mRNA processing. CPSF3 (also called CPSF73) is the enzyme that cleaves the substrate at the polyadenylation site.…”
Section: Mrna Processing and Exportmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzoxaborole acoziborole is undergoing clinical trials for sleeping sickness treatment [113], and other benzoxaboroles are under consideration for other kinetoplastid diseases [114]. The first detectable effect after treatment of T. brucei with the benzoxaborole AN7973 is an increase in mRNA precursors and a decrease in the Y-structure intermediate [3], suggesting that this compound targets mRNA processing. CPSF3 (also called CPSF73) is the enzyme that cleaves the substrate at the polyadenylation site.…”
Section: Mrna Processing and Exportmentioning
confidence: 99%
“…Because of this, comparisons between the different models enable us to distinguish characteristics that were present in the last eukaryotic common ancestor from those that evolved later [2]. Moreover, one aspect of trypanosome gene expression—their mRNA processing—is a target of clinically useful drugs for the treatment of human and ruminant trypanosomiasis [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 89 , 91 and 92 were later established to be orally efficacious leads for stage 1 and 2 HAT in murine models, with compound 92 progressing into the clinic . While the MOA is yet to be fully elucidated, several related studies have shed light on several possible MOAs . Possibly the most significant in this regard was an orthogonal proteomic and genomic study which identified 14 protein targets of 93 .…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 99%
“…Over-expression of the gene yielded a notable loss of activity [96]. Elegant experiments using a gene over-expression library, followed by a selection of clones over-expressing genes yielding reduced sensitivity to acoziborole itself, also identified CPSF3 [97], and over-expression confirmed loss of sensitivity, pointing to CPSF3 as a target, if not the exclusive target, of these compounds in trypanosomes.…”
Section: Acoziborole: Mode Of Action and Resistance Riskmentioning
confidence: 91%
“…Subsequently, CPSF3 was identified as a target for benzoxaboroles in apicomplexan parasites Plasmodium [93] and Toxoplasma [94]. Based on this observation, and the fact that metabolomics experiments had revealed a profound change in the methionine metabolism [95] that might have been related to RNA processing defects, particularly given the multi-methylation of the spliced leader sequence used in trans-splicing in trypanosomes, the effect of over-expression of CPSF3 on sensitivity to the related benzoxaborole, AN7973, was tested [96].…”
Section: Acoziborole: Mode Of Action and Resistance Riskmentioning
confidence: 99%